(3chcH GdeHGfi hehcH GdeYGfi aj TQM UdhGJ GdTjN YHO GdbGOQ GdcjdGfis - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hcai f hSdGe Ydi YHGOgY GdPjf EUWai , CeG HYO agPG TQM Wdja hSQM dWja GdNjGd GdeWja cTa Hg YHO GdZfi YeG JVefg GdeJf s
(3BNQgG (B:s
(3hdfNJe cJGHfG gPG HbUjOI feOM TjNfG GdePchQ YHO GdbGOQ TjN GdhbJ hGdMVhQ QaY Gddg QGjGJ eLOg hfTQ ai GdNGabjf CYdGeg Bejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B593s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B394s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs